Urgensi Edukasi Antibiotik: Tingkat Pengetahuan dan Praktik Swamedikasi di Puskesmas Makkasau - Imam Adrian Rakhman; Pandi Prata Suanda; Muhammad Nur Ikhwan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Background: Antibiotics are essential medicines for treating bacterial infections; however, inappropriate use has become a major driver of the global rise in antibiotic resistance, leading to reduced treatment effectiveness, increased healthcare costs, and higher mortality risk. In Indonesia, resistance to various classes of antibiotics, such as β-lactams and macrolides, has increased significantly in recent years. Prior studies indicate that public knowledge levels substantially contribute to irrational antibiotic use. Puskesmas, as primary healthcare facilities, play a strategic role in education and health promotion regarding prudent antibiotic use. Methods: This descriptive observational study employed a questionnaire to assess patients’ knowledge of antibiotic use at Puskesmas Makkasau. Respondents were selected through convenience sampling, and data were analyzed using frequency distributions to identify knowledge levels. Result: The findings show that most respondents exhibited inadequate knowledge and inappropriate attitudes toward antibiotic use. Conclusion: The majority of visitors to Puskesmas Makkasau had low levels of knowledge about antibiotic use, with persistent misconceptions, such as believing antibiotics cure viral infections; and common practices of sharing, storing, and using antibiotics without a physician’s prescription.